Detection of Parental Contribution to Molar Genome Leads to Diagnosis of Recurrent Hydatidiform Mole in a Family with NLRP7 Variants. (1st June 2022) - Wang, Rong-Yue; Li, Yu-Juan; Zhen, Li; Jiang, Fan; Gu, Cong-Min; Li, Dong-Zhi
Abstract: Introduction: Genetically, complete hydatidiform mole (CHM) is androgenetic diploid, containing two sets of paternal chromosomes. In most cases, recurrent HM (RHM) is CHM but has diploid biparental chromosome constitution. Case report: We report a mother with RHM, both with biparental diploidy. The mother was compound heterozygous for two variants, c.1720dup, p.(C574Lfs*4) and c.2165A > G, p.(D722G) of the NLRP7 gene, as was a brother who fathered 2 normal pregnancies. Conclusion: The genotype study should be obtained for patients of CHM, even in their first pregnancy, followed by genetic screening for maternal-effect variants in those with biparental moles. This strategy will identify patients in their first pregnancy with HM that have a decreased chance for a normal pregnancy, to allow genetic counseling, perhaps utilizing a donor egg.